Regional Workshop on African Agriculture in a Changing Climate - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
This regional workshop provided an opportunity for consolidating and sharing of experiences that could inform the emerging CSA global efforts and the on-going UNFCCC negotiations.